Macroprudential capital requirements with non-bank finance - Kyle P. Dempsey (European Central Bank (ECB), 2020)
I analyze the impact of raising capital requirements on the quantity, composition, and riskiness of aggregate investment in a model in which firms borrow from both bank and non-bank lenders. The bank funds loans with insured deposits and costly equity, monitors borrowers, and must maintain a minimum capital to asset ratio. Non-banks have deep pockets and competitively price loans. A tight capital requirement on the bank reduces risk-shifting and decreases bank leverage, reducing the risk of costly bank failure. In response, though, the bank can change both price and non-price contract terms. This may induce firms to substitute out of bank finance, leading to a theoretically ambiguous effect on the profile of aggregate investment. Quantitatively, I find that the bank's incentive to insure itself against issuing costly equity and competition from the non-bank sector mutes the long run impact of raising capital requirements. Increasing the capital requirement from 8% to 26% eliminates bank failures with effectively no change in the quantity or riskiness of aggregate investment.
Keywords: G2; E5; E6; E32; E44; 330; banking; capital requirements; business cycles